Excess protons in mesoscopic water-acetone nanoclusters - Semino, R. (2012)
We carried out molecular dynamics simulation experiments to examine equilibrium and dynamical characteristics of the solvation of excess protons in mesoscopic, [m:n] binary polar clusters comprising m 50 water molecules and n 6, 25, and 100 acetone molecules. Contrasting from what is found in conventional macroscopic phases, the characteristics of the proton solvation are dictated, to a large extent, by the nature of the concentration fluctuations prevailing within the clusters. At low acetone contents, the overall cluster morphology corresponds to a segregated aqueous nucleus coated by an external aprotic phase. Under these circumstances, the proton remains localized at the surface of the water core, in a region locally deprived from acetone molecules. At higher acetone concentrations, we found clear evidence of the onset of the mixing process. The cluster structures present aqueous domains with irregular shape, fully embedded within the acetone phase. Still, the proton remains coordinated to the aqueous phase, with its closest solvation shell composed exclusively by three water molecules. As the relative concentration of acetone increases, the time scales characterizing proton transfer events between neighboring water molecules show considerable retardations, stretching into the nanosecond time domain already for n ∼ 25. In water-rich aggregates, and similarly to what is found in the bulk, proton transfers are controlled by acetone/water exchange processes taking place at the second solvation shell of the proton. As a distinctive feature of the transfer mechanism, translocation pathways also include diffusive motions of the proton from the surface down into inner regions of the underlying water domain. © 2012 American Institute of Physics.